EFEKTIVITAS MEDIA FILM BILAL: A NEW BREED OF HERO DALAM MENINGKATKAN NILAI-NILAI TAUHID DI KALANGAN SISWA SMP - AHMAD SAYYIDIMAN HAMIDALLOH; Laily Abida (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to determine the effectiveness of the film Bilal: A New Breed of Hero (2015) in enhancing students’ understanding of the values of monotheism (tauhid). The background of this study is the need for innovative and engaging learning media to help students deeply compre-hend the concept of tauhid This research uses a quantitative approach with a true experimental method and a pre–test post–test control group design. The subjects of this study were 26 students of class 7A at SMP Islam Al Maarif 01 Singosari. Data collection techniques included pre–tests, post–tests, observation, and interviews. The results showed a significant increase in students' understanding of the values of tauhid after watching the film. It can be concluded that the film is effective as a learning medium in improving students’ understanding of monotheism values. This research recommends the use of Islamic films as an alternative learning medium in Islamic Religious Education subjects.